Anthropometrics characteristics and jumping ability in basketball - Altavilla, G.; D'Isanto, T.; Di Tore, P. A. (Journal of Human Sport & Exercise, 2018)
The basketball is a situational sport classified among activities laying on alternative aerobe and anaerobic processes, with an important participation of the muscular mass and an accentuated prevalence of the alactacid anaerobic process. The purpose of this work is to analyze and evaluate the correlations between the various variables of an anthropometric character and the differences in performance between the roles, testing a group of senior high-level basketball players, subdividing them according to their role within of the team. Data were collected by 40 basketball players (Senior elite), divided into four groups: Power Forward (n = 12; age = 24.5 + 1.4 y.), Pivot (n = 12; age 24.1 + 1.1 y.); Playmaker/Guard (n = 8; age = 24.4 + 1.3 y.), and Small Forward (n = 8; age = 23.5 + 1.2 y.). Morphological data were height, weight, body mass index (BMI), Abalakov test modified. The explosive strength was measured with the method of Bosco: squat jump (SJ), counter movement jump (CMJ) and CMJ with arms (CMJas). Jumping performance and of coordination was determined through the difference between the measurement on the technical action of the shot block with one hand (St) and the height with one stretched arm (AB1); then, the measurement of the technical action of the rebound at two hands (Rb) and the height with two stretched arms (AB2). The results of the anthropometric parameters showed significant differences in height (F = 4.75, p <0.006), height with a stretched arm AB1 (F = 3.60; p <0.02) and height with two stretched arms AB2 (F = 3.66; p <0.02). In the comparison by role we did not obtain any statistical significance regarding the Bosco test. Results of Abalakov test modified showed significant differences in St (F = 7.29; p<.001) and in Rb (F = 3,95; p <0.01). With the Bosco test the information obtained concerns the assessment of the athlete's jumping capacity not related to specific technical gestures; differently with the Abalakov Test, has provided precise indications on the elevation abilities connected to the technical gesture of the blocked shot and of the rebound. A high correlation was found between the results of the anthropometric parameters and those of the Abalakov test. In senior high-level basketball, the anthropometric profile of the players is directly related to specific variables which must be used for training planning and for the choice of players in setting up a team. Modern basketball, due to the increasing intensity of the game rhythm, increasingly engages the anaerobic alactacid component; it is above all for this reason that we need more and more powerful athletes, who are both fast and capable of high performance in jumps. This is the reason why assessment, training and continuous monitoring of jumping skills are a decisive aspect of performance.